2019
DOI: 10.1016/j.jsams.2018.11.027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 1,3-butanediol and carbohydrate supplementation on running performance

Abstract: Objectives: Ingested ketogenic agents offer the potential to enhance endurance performance via the provision of an alternative exogenous, metabolically efficient, glycogen-sparing fuel (i.e. ketone bodies). This study aimed to assess the impact of combined carbohydrate and 1,3-butanediol (CHO-BD) supplementation on endurance performance, blood beta-hydroxybutyrate (βHB) concentration and glycolytic activity, in comparison to carbohydrate supplementation alone (CHO). Design: Eleven male runners (age 38 ± 12 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(85 citation statements)
references
References 28 publications
(35 reference statements)
7
68
0
7
Order By: Relevance
“…We found that neither administration nor dose of βHB+MCT in uenced heart rate, RR, RER, VO 2 , VCO 2 , VE, or estimated metabolic oxidation rates. HR has elevated with ketone salts administration [15,16] or reductions in HR with ester administration [18,20], with the vast majority consistent with our ndings across exogenous ketone supplements [19,[21][22][23]25]. While most exogenous ketone evaluations have not observed changes in RER in agreement with our observations, some analyses have observed differences [8,13,14].…”
Section: Cognitive Performancesupporting
confidence: 87%
See 4 more Smart Citations
“…We found that neither administration nor dose of βHB+MCT in uenced heart rate, RR, RER, VO 2 , VCO 2 , VE, or estimated metabolic oxidation rates. HR has elevated with ketone salts administration [15,16] or reductions in HR with ester administration [18,20], with the vast majority consistent with our ndings across exogenous ketone supplements [19,[21][22][23]25]. While most exogenous ketone evaluations have not observed changes in RER in agreement with our observations, some analyses have observed differences [8,13,14].…”
Section: Cognitive Performancesupporting
confidence: 87%
“…*** Figure 4 Goes here*** Discussion A consistent nding across all exogenous ketone bodies is their ability to induce rapid and widespread changes in metabolism, including consistent changes in circulating metabolic concentrations, ketones, glucose, lactate, amino acids, and/or free-fatty acids. Unsurprisingly, all analyses to date have demonstrated that exogenous ketones signi cantly elevate circulating blood ketones, although to differing extents pending the exogenous agent [5,8,[13][14][15][16][17][18][19][20][21][22][23]. Synthetic 1,3 BD and/or esters raise R-βHB to a greater extent than ketone salts [3,6].…”
Section: Cognitive Performancementioning
confidence: 99%
See 3 more Smart Citations